Assessment of Neurocognitive Effect in Patients Undergoing Cardiopulmonary Bypass: A Prospective Longitudinal Study - Ahmed Jamal, Usman Javed Iqbal, Aroosa Amjad, Rabia Javed Iqbal, Abrar Hussain, Hassan Abbas Abdullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess neurocognitive effects in patients who underwent cardiopulmonary bypass. Study Design & Setting: Using non probability purposive sampling, a prospective study design was used to collect the data from in tertiary care hospitals with 60 beds in ICU. Methodology: Patients who underwent CPB having no history of psychological and mental illness was recruited for the said study. We used a short test of global mental status to measure cognitive performance called the “Mini-Mental State Examination (MMSE)”.Wilcoxon test was used to analyze the pre- and post-operative changes over MMSE. The Folstein test, often known as the mini-mental state examination (MMSE), is a 30-point survey that has been widely used in clinical and research contexts to evaluate cognitive impairment. Different parameters; temporal, spatial, alternate, recognition, and recall were evaluated. P-value ≤0.05 was considered as significant. Results: In this study, a significant fall in spatial, temporal, short term recall, long term recall, object recognition, alternate, reading, writing, read and act, and drawing in post-operative MMSE scores was observed as compared to pre-operative. However, there was no significant change in command so there is little or no effect on command parameters in pre-operative and post-operative cardiopulmonary bypass patients. There was a significant difference between pre-operation and post-operation total scores i.e., a fall in the ‘total’ score of neurocognition occurred after cardiopulmonary bypass. Practical implication Study finding may be used for practical implications in managing neurocognitive outcome in patients undergoing cardiopulomonary bypass. Conclusion: This research concludes that neurocognition is affected in patients who underwent CPB, with CPB itself a bigger risk factor in causing postoperative neurocognitive dysfunction. Keywords: Cardiopulmonary bypass, Mental health, Neurocoagnitive impairment, POCD